Segmenting Supply Chain Process for Optimal Performance by Adopting Postponement: A Randomized Trial - Rahman, Md. Ziaur (International Journal of Supply Chain Management, 2018)
Even though extensive technologies have been applied to all stages of a supply-chain, the performance of many supply chains has been quite dismal. One potential cause for failure is the lack of comprehending the nature of the demand and therefore being unable to device a supply-chain that would better satisfy that demand. A common mistake is to use an efficient supply chain that calls for a responsive supply chain and vice versa. The paper aims to develop the first wave of empirical investigations related to the impact of supply chain design practices on performance. It investigated a supply chain design model that linked efficiency with responsiveness to optimize performance by deploying postponement. An inâdepth case study methodology was adopted to uncover the strategies undertaken by one of the Bangladeshs fastest growing cement manufacturers to create a competitive advantage through its management of the supply chain design alignment. The major elements were verified by surveys. Applicability and exploitability of the diagnostic instrument was validated using action research. Generally, the adoption of segmenting the supply chain process by diffusing the postponing style led to an improved performance, which, in turn, positively impact operational performance. Operational performance enhances organizational performance. Just as processes can be broken into parts, so can supply-chain processes be segmented to achieve optimal performance. Practitioners are provided with a framework for assessing the synergistic impact of postponing practices on supply chain design performance.   Keywords: Action Research on Supply Chain, Alignment, Efficient, Responsive, Optimal Performance, Postponement, Supply-chain design.